Conciliar Christology - Timothy Pawl (St Andrews Encyclopaedia of Theology)
This article presents the concept of Conciliar Christology, the Christology taught at the first seven ecumenical councils of the Christian Church. It then discusses the motivations for considering Conciliar Christology when theorizing about the incarnation. These motivations include the historical groundedness one gains in theorizing in light of Conciliar Christology, the broad consensus of reception and authority that Conciliar Christology enjoys among Christians throughout the centuries, and the relevance Conciliar Christology has to the community of Christian believers. It next discusses the foundations of Conciliar Christology as they were taught by the ecumenical councils. Those councils themselves relied on multiple sources in their formation of doctrine, with their main two sources being scripture and tradition. Concerning traditional sources, the councils cite historical practice, previous conciliar teaching, and the texts of their opponents (as a sort of negative source of authority). After discussing the concept, the motivation, and the foundations for Conciliar Christology, the article summarizes the content of Conciliar Christology. According to Conciliar Christology: